Keadilan Organisasi dan Lingkungan Kerja Non Fisik Dalam Meningkatkan Kepuasan Kerja Melalui Motivasi Intrinsik pada PT Tunggal Djaja Indah Sidoarjo - Kurniawati, Safitri Dwi; Abadiyah, Rifdah (Innovative Technologica: Methodical Research Journal, 2023)
The purpose of the following study is to describe and analyze the variable of organizational justice and non-physical work environment in increasing employee job satisfaction through intrinsic motivation at PT Tunggal Djaja Indah Sidoarjo. In this study, using quantitative research methods, data collection was distributed through questionnaires, with samples using saturated samples, where there were 60 respondents at PT Tunggal Djaja Indah Sidoarjo. The data analysis used data quality testing techniques, descriptive statistical analysis, classical assumption test, and hypothesis testing using T test, F test, coefficient of determination test (R2), and path analysis. The data processing uses SPSS version 22 software. Primary data collection is carried out by spreading questionnaires which are measured using an interval scale, which is tested using validity and reliability tests.